A modified CRISPR/Cas9 approach in silencing the triplication in Down syndrome: A treatment path XISTs - Gewei Lian; Abdalla Khabazeh; Volney Sheen (Proceedings of the National Academy of Sciences, 2026)
Down syndrome (DS) is one of the most common developmental human genetic disorders and is due to triplication of chromosome 21 (HSA21). Although previous studies using epigenetic suppression of HSA21 by the long noncoding RNA XIST showed a potential for DS treatment, integration efficiency of XIST by conventional zinc finger nucleases is too low to allow for practical implementation. Here, we report a modified CRISPR/Cas9 approach, which enhances the efficiency of XIST gene integration. First, a codon-optimized λ-phage exonuclease (exo) was fused with Cas9 to create 5’- and 3’-end overhangs at cutting sites of donor DNA and acceptor chromosome DNA. Second, four sgRNAs, two of which selectively targeted each the acceptor or donor DNA, were assembled tandemly into one Cas9 plasmid (PX459) to increase the Cas9-cutting efficiency and promote donor DNA integration. Third, sgRNAs were designed by searching for unique single nucleotide polymorphism nucleotides distinct between the three HSA21 copies, as a protospacer adjacent motif site to specifically target one HSA21 copy. Fourth, donor DNA plasmid containing XIST was modified to disable replication and inhibit transcription function and allow for inducible expression. Our modified CRISPR method significantly enhanced the integration efficiency (20 to 40%) of long XIST gene (14 kb) into an extra chromosome 21 (HSA21), as was identified with PCR, cell cloning, immunostaining, and FISH. RNA sequencing results showed that imbalance of gene transcription across extra HSA21 can be partially corrected by XIST gene integration. The modified CRISPR method with XIST paves a road for therapeutic treatment for DS.